Peran dan Efek Fatwa Majelis Ulama Indonesia (MUI) di Tengah-Tengah Masyarakat - Yasin, Nur; Muhamad Shobirin; Siti Amina (HOKI : Journal of Islamic Family Law, 2025)
as a fatwa institution needs to synergize with related institutions and the government in carrying out its mandate, so that it can work with strong power. And the MUI in Indonesia will be faced with the diverse characters of a multicultural society. Another factor is that the Muslim community in Indonesia was created due to the da’wah process, so the MUI must be involved in the world of da’wah in order to build closeness with the community. Because Indonesian society is an Eastern society that upholds morals or good manners, the appropriate preaching for them is philanthropic preaching that prioritizes humanity and compassion. If the MUI is supported by the government, severa related institutions and enters the hearts of the people, it will have a good effect on its fatwa and it will even become an elegant fatwa in society